Поэтика ранневизантийской литературы - Аверинцев Сергей Сергеевич (Coda, 1997)
Экземпляры: ФИЛ (20001113) / Инвентарный номер: 1037061 / Цена: 22.00 / Сис.шифр: 83.3(0) / Авт.знак: А 19 / ГРНТИ: 17 / ББК: 83.3(0)42